BrachyView, a novel in‐body imaging system for HDR prostate brachytherapy: Experimental evaluation. Issue 12 (19th November 2015) - Safavi‐Naeini, M.; Han, Z.; Alnaghy, S.; Cutajar, D.; Petasecca, M.; Lerch, M. L. F.; Franklin, D. R.; Bucci, J.; Carrara, M.; Zaider, M.; Rosenfeld, A. B.
Abstract : Purpose: This paper presents initial experimental results from a prototype of high dose rate (HDR) BrachyView, a novel in‐body source tracking system for HDR brachytherapy based on a multipinhole tungsten collimator and a high resolution pixellated silicon detector array. The probe and its associated position estimation algorithms are validated and a comprehensive evaluation of the accuracy of its position estimation capabilities is presented. Methods: The HDR brachytherapy source is moved through a sequence of positions in a prostate phantom, for various displacements in x, y, and z . For each position, multiple image acquisitions are performed, and source positions are reconstructed. Error estimates in each dimension are calculated at each source position and combined to calculate overall positioning errors. Gafchromic film is used to validate the accuracy of source placement within the phantom. Results: More than 90% of evaluated source positions were estimated with an error of less than one millimeter, with the worst‐case error being 1.3 mm. Experimental results were in close agreement with previously published Monte Carlo simulation results. Conclusions: The prototype of HDR BrachyView demonstrates a satisfactory level of accuracy in its source position estimation, and additional improvements are achievable with further refinement of HDR BrachyView 's image processing algorithms.